Development Of A Lineric Learning Model To Improve Students' Literacy And Numeracy - Diana Silaswati; Neneng Maelasari; Emas Marlina (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
This study aims to develop a LINERIC learning model designed to improve junior high school students' literacy and numeracy skills. The LINERIC learning model is a conceptual integration between the Reading to Learn approach that emphasizes strengthening reading comprehension literacy and Computational Thinking that emphasizes strengthening literacy and numeracy. The Lineric learning syntax is Literacy Activation, Information Mining, Numeracy Decomposition, Equation Construction, Reasoning Communication, Interpretation & Reflection and Consolidation. This study uses a design and development research (DDR) design with three stages: (1) problem analysis, (2) design and development, and (3) evaluation. The research instruments include expert validation sheets, teacher and student practicality sheets, and context-based literacy and numeracy tests. The results of the study indicate that: (1) the LINERIC learning model is considered very valid by experts from the aspects of theoretical rationale, syntax, usability, and feasibility of implementation; (2) the model is in the very practical category based on teacher and student responses; and (3) there was a significant increase in literacy and numeracy skills after implementing the LINERIC learning model in a limited trial class (N = 32). The results of the study showed that the LINERIC learning model developed was very valid and feasible to be implemented with the results of the material expert validation reaching an average score of 96.48%, and the media expert validation reaching 95.25%, both of which were categorized as very high. The practicality test showed a very positive response, with an average teacher response of 96% and a student response of 98%. Furthermore, the effectiveness test showed a high N gain score of 0.79 for literacy and 0.78 for numeracy, which indicated a significant increase in both competencies.